2014
DOI: 10.1021/ma501085c
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Polymerization of Isoprene by Using NSN- and NPN-Ligated Rare Earth Metal Precursors: Switching of Stereo Selectivity and Mechanism

Abstract: The rare-earth metal complexes bearing NSN-bidentate β-diimidosulfonate ligands (RNSN dipp )Ln-(CH 2 SiMe 3 ) 2 (THF) n (R = Ph, Ln = Lu (1a), n = 1, Y (1b), n = 2, Sc (1c), n = 1; R = PhNMe 2 , Ln = Lu (1d), n = 1) were synthesized by treatment of the ion-pairs [Ln(CH 2 SiMe 3 ) 2 (THF) x ][BPh 4 ] with equimolar amount of the ligand lithium salts (RNSN dipp )Li(THF) 2 (NSN dipp = S(NC 6 H 4 i Pr 2 -2,6) 2 ). Addition reaction between lutetium tris(alkyl)s, Ln(Z) 3 (THF) n and NSN dipp gave the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 80 publications
3
52
1
Order By: Relevance
“…33,64 The activities are broadly in line with most other Co complexes, once the superior effect of EASC over DEAC is taken into account, which is to say, in the range of hundreds to a few thousands of mol IP mol À1 catalyst h À1 . It becomes clear that catalysts 5-7 are moderately active; much more active than cationic 61 or anionic polymerizations, 62 more active that nickel salts, 20 more active than some lanthanum and lanthanide catalysts, 63 but less active than most.…”
Section: Catalyst Performance Comparisonsupporting
confidence: 52%
See 1 more Smart Citation
“…33,64 The activities are broadly in line with most other Co complexes, once the superior effect of EASC over DEAC is taken into account, which is to say, in the range of hundreds to a few thousands of mol IP mol À1 catalyst h À1 . It becomes clear that catalysts 5-7 are moderately active; much more active than cationic 61 or anionic polymerizations, 62 more active that nickel salts, 20 more active than some lanthanum and lanthanide catalysts, 63 but less active than most.…”
Section: Catalyst Performance Comparisonsupporting
confidence: 52%
“…Historically and currently, Ziegler-Natta catalysts have oen been used in the polymerization of 1,3-dienes; 9-11 however, molecular catalysts have also met with wide interest. It is now possible to obtain high trans-1,4 polymer, 16,28-30 high 3,4isotactic polymer [31][32][33] and high 3,4 atactic or syndiotactic polymer, 34 mostly with lanthanides, but it is also possible to obtain unique cis-1,4-alt-3,4 polyisoprene with cobalt phosphine complexes. 12,13 The key modes of enchainment of polyisoprenes are shown in Chart 1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CpTiCl 3 was used for cis ‐1,4 living polymerization of butadiene and its biphenolate derivatives for copolymerization of isoprene with styrene . Lanthanide complexes reported by Hou and Cui group had been successfully used for cis ‐1,4, trans ‐1,4, syndiotactic 3,4‐polymerization of isoprene . As Brookhart and Gibson reported their seminal work of α‐diimine‐Ni/‐Pd ligands and bis(imino)pyridine‐Co/Fe catalysts, researchers have revisited the first‐row of d‐block elements due to their long‐term availability .…”
Section: Introductionmentioning
confidence: 99%
“…Cui and co‐workers found that the complexes 113 Lu and 117 (Figure ), upon the activation with [PhMe 2 NH][B(C 6 F 5 ) 4 ] and Al i Bu 3 , provided PIP with high 3,4‐selectivities, but the isoselectivities were different . The complex 113 Lu gave a distinguished isospecific selectivity ( mm =96 %, mmmm =96 % in chlorobenzene at −30 °C), while the more bulky NPN‐ligated complex 117 gave moderate syndiotactic PIP ( rr =59 %, rrrr =32 %) under the same conditions.…”
Section: Stereoselective Polymerization Of Conjugated Dienesmentioning
confidence: 99%